Consideraç\~oes complementares sobre o financiamento da previdência social no Brasil: Estimativas de alíquotas necessárias e impactos do Microempreendedor Individual (MEI) - Rogério Nagamine Costanzi; Graziela Ansiliero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The pension reform carried out in 2019 consists of the most extensive reformulation of the Brazilian social insurance system since the promulgation of the 1988 Federal Constitution. Despite important changes and advances in sustainability in the medium and long terms, from the expenditure perspective, major challenges persist for the future financing of the social insurance system. There is a need for a deeper debate regarding the financing of the social insurance and social security systems, given the process of rapid and intense population aging and other issues - such as the expansion of the individual microentrepreneur (MEI) - that add pressure to the current funding model. This Discussion Paper presents estimates on the necessary rates to fully fund the social insurance system, guaranteeing financial e actuarial sustainability. In addition to estimating what the necessary rate would be, it is necessary to consider the various differentiated subsystems within the General Social Insurance Scheme (RGPS) - actuarially highly subsidized, such as the MEI - which, strictly speaking, raise this necessary rate, in addition to other issues. It is also worth highlighting the Brazilian rural pension, also within the scope of the RGPS, which is also quite unbalanced and generates relevant impacts on the overall financing of the Brazilian social insurance scheme. The present study seeks to complement the Discussion Papers No. 2981 and No. 2988, which also dealt with the issue of social insurance financing.
Keywords: H55; 330; social security/pension financing; rates for full funding; actuarial balance and individual microentrepreneur